Odpowiedź :
Odpowiedź:
zad 1
1)
(2x - 3y)(- x + 5y) = - 2x² + 3xy + 10xy - 15y² = - 2x² + 13xy - 15y²
2)
(- 2a + 3b)(8a - 5b) = - 16a² + 24ab + 10ab - 15b² = - 16a² + 34ab - 15b²
3)
(- a + 3b)(a² - 5b) = - a² + 3a²b + 5ab - 15b²
zad 2
1)
a(2a + 5) - x
2)
(2k + b)²
zad 3
1)
(25y - 30) : 5 = 25y/5 - 30/5 = 5y - 6
2)
(- 8 + 12y) : ( - 2 ) = - 8/(- 2) + 12y/(- 2) = 8/2 - 6y = 4 - 6y
Odpowiedź:
ZAD 1.
1. -2x^2 + 13xy - 15y^2 2. -16^2 + 34ab - 15b^2 3. -2a^2 + 11ab - 15b^2
ZAD 2.
Sory, ale strasznie mi się nie chce bo dopiero wstałem
ZAD 3.
1. -(5y-6)
2. 4-6y